Manajemen Kandang Broiler di CV. Mjj Blessindo Farm Desa Winong Lor Kecamatan Gebang Kabupaten Purworejo - Maharsi Nasywa Madina; Oktavia Rahmawati (Mikroba : Jurnal Ilmu Tanaman, Sains Dan Teknologi Pertanian, 2024)
Cage management is vital for farmers because it is related to providing a comfortable environment for broiler chickens. A study was conducted in CV. Mjj farm blessindo to find out the location, layout, and equipment needed in broiler maintenance in a close-house cage. The data collection methods consist of primary data and secondary data. Primary data includes the results of observations and interviews, while secondary data comes from maintenance management guidebooks and scientific articles. The results of the study indicate that the Mjj farm blessindo cage is well managed from all aspects so that the chicken's performance and production produce satisfactory values.